Culture and financial literacy: Evidence from a within-country language border - Brown, Martin; Henchoz, Caroline; Spycher, Thomas (Journal of economic behavior & organization, 2018)
•We study the effect of cultural background on financial literacy.•We comparing secondary-school students along the German-French language border within the same institutional setting in Switzerland.•We document that students in the French-speaking area have a much lower level of financial literacy than students in the German-speaking area.•We show that the cultural divide in financial literacy is related to systematic differences in financial socialisation by parents (e.g. pocket money). We study the effect of culture on financial literacy by comparing secondary-school students along the German–French language border within Switzerland. We find that students in the French-speaking region have a lower level of financial literacy than students in the German-speaking region. The difference in financial literacy across the language groups is stronger for native students and monolingual students than for immigrant students and bilingual students. This supports the hypothesis that embedded cultural differences rather than unobserved heterogeneity in schooling are driving the effect. A mediation analysis suggests that the cultural divide in financial literacy is related to systematic differences in financial socialisation across the language groups. Students in the German speaking region are more likely to receive pocket money at an early age, and are more likely to have independent access to a bank account than students in the French speaking region.